MANAGEMEN PENINGKATAN MUTU TENAGA PENDIDIK DAN KEPENDIDIKAN BERBASIS STANDAR NASIONAL PENDIDIKAN DI MTS NEGERI MODEL PARE - Misbahuddin, - (Al Tadib : Jurnal Ilmu Pendidikan, 2014)
MTsN Pare is accredited "A" and as a madrasah “model”, MTsN Pare always develop in a sustainable national standard. This is where researchers examine the improvement of energy management educator and national educational standards-based education. In this research, the writer uses descriptive qualitative method with the method: 1) in depth interview, 2) Participants observation. 3). Documentation study. The results of this study: 1.Strategy done in improving the quality of madrasah is: (a) forming a work team in a madrasah (b) find a reliable committee in accordance with the needs of education (c) self-evaluation or self-assessment (d) to formulate a vision and mission (e ) plan purposes (f) the implementation of goals, which involve the role of the principal, teachers, parents and the community (g) evaluate the purpose of (h) to report on the purpose of which was to be implemented. 2 In the implementation of the implementation of the national education standard 8 components are suitable with BSNP (a) the standard content, which is in the document of curriculum ready to be implemented and each teacher has a teaching device, the expansion of an existing self-structured form of the last chapter and all short letters. (b) the standard process, the learning process according to BSNP, teachers already have the lesson plan, (c) the standard of competence graduates already laid the foundations of intelligence, knowledge, personality and independence, and extend to the quality of the school. (d) the standard of teachers and education staff, have appropriate academic qualifications at least under graduate and graduate program although there are some outstanding and to have the appropriate educational staff with BSNP.Keywords: management, teachers and education staff, SNP.